The Genetics of Keratoconus - Nowak, Dorota M. (Medknow Publications, 2011)
Keratoconus (KTCN) is non-inflammatory thinning and anterior protrusion of the cornea that results in steepening and distortion of the cornea, altered refractive error, and decreased vision. Keratoconus is a complex condition of multifactorial etiology. Both genetic and environmental factors are associated with KTCN. Evidence of genetic etiology includes familial inheritance, discordance between dizygotic twins, and association with other known genetic disorders. Several loci responsible for a familial form of KTCN have been mapped; however, no mutations in any genes have been identified for any of these loci. This article focuses on the genetic aspects. In addition, bioinformatics methods applied in KTCN gene identification process are discussed.